EFFECT OF MALTOSE CONCENTRATION IN TRIS DILUTION ON EPIDIDYMAL SPERMATOZOA QUALITY OF BALI BULL PRESERVED AT 50C - Wattimena, J.; Parera, F.; Veerman, M. (Journal of the Indonesian Tropical Animal Agriculture, 2009)
The objective of research was to evaluate the effect of maltose concentration in Tris dilution onepididymal spermatozoa quality of Bali bull that preserved at 50C. Five testis of Bali bull collected fromslaughter house were used in this study. Epididymal spermatozoa were collected through slicing andflushing methods, pressing cauda epididymal was conducted in NaCl physiology (NaCl 0.9%) emulsion.Spermatozoa which collected were divided into three reaction tube and each diluted by Tris dilutioncontaining: Tris dilution + 20% of yolk (control); Tris dilution + 20% of yolk + 0.3 g of maltose/100ml(M0.3); and Tris dilution + 20% of yolk + 0.6 g maltose/100 ml (M0.6). Spermatozoa qualities observedwere motile spermatozoa (MS), live-spermatozoa (LS) and intact-plasma membrane (IPM) thatevaluated daily in refrigerator at temperature of 5oC. Completely Randomized Design with threetreatments and five replications was used in this study. Data was analyzed by analysis of variance.Examination on fresh spermatozoa showed that spermatozoa concentration was 11,222.5 million cell/ml,motile spermatozoa was 75.00%, live-sperm was 86.75%, abnormal spermatozoa was 10.50%,cytoplasmic droplet was 14.00% and IPM was 86.75%. At the seventh day of preservation, thepercentages of MS, LS and IPM in M0.3 were 37.0 %, 49.2% and 50.4%, respectively, and M0.6 were38.05%; 51.8 % and 52.0%, respectively that were significantly higher (P<0.05) than control (29.0%;41.8% and 42.4%, respectively). It was concluded that maltose added into Tris dilution could lengthenepididymal spermatozoa quality of Bali bull which persevered at 50C.